Simple Adaptive Control-Based Reconfiguration Design of Cabin Pressure Control System. (30th March 2021) - Zhang, Zhao; Yang, Zhong; Xiong, Si; Chen, Shuang; Liu, Shuchang; Zhang, Xiaokai
Abstract : The Cabin Pressure Control System (CPCS) is an essential part of the aviation environmental control system that ensures aircraft structure and flight crew safety. However, the CPCS usually has potential faults of sensors and actuators. To this end, a Simple Adaptive Control- (SAC-) based reconfiguration method is proposed to compensate for the above adverse effects. Some good pressure control performance of CPCS can be achieved by the basic pressure controller when the system is in normal operation. A parallel feedforward compensator is designed to guarantee the closed-loop system's stability and the almost strictly positive realness of the augmented system. Thus, the simple adaptive controller can be utilized for the CPCS. In particular, the reconfiguration system can update the control law online when the fault occurs without the system identification process. The reference model is obtained by mathematical model linearization after considering the mechanical characteristics of the CPCS. Extensive simulations under various typical fault scenarios are carried out throughout the entire flight envelope of the aircraft from take-off to landing. Simulation results validate the robustness and reconfiguration control capability of the proposed method.